Frozen storage of lesser mealworm larvae (Alphitobius diaperinus) changes chemical properties and functionalities of the derived ingredients. (1st August 2020) - Wessels, M.L.J.; Azzollini, D.; Fogliano, V.
Highlights: Molecular changes in Lesser mealworms occur within one week of storage at −20 °C. Enzymatic activity in Lesser mealworms is still possible at −20 °C. A significant proteolysis occurs during the first week of storage at −20 °C. Browning reaction and foaming increase upon prolonged frozen storage. Abstract: The effect of frozen storage on the chemical properties and ingredient functionalities of Lesser mealworms was investigated at −20 °C for 2 months. Major changes occurred in the first week of frozen storage. Proteins, among which heavy chain myosin, underwent denaturation and aggregation, as shown by a decrease in solubility, SDS-PAGE pattern, and Confocal Laser Scanning Microscopy. The ice melting point in larvae was −32.5 °C as determined by DSC: 25% of water is not frozen at −20 °C, possibly due to anti-freezing proteins preventing ice formation. The presence of unfrozen water favoured various enzymatic activities as shown by a pH decrease, indicating protein hydrolysis. The molecular changes during frozen storage increased the browning reactions due to phenoloxidase activity. Foaming ability, foam stability and gel network stability increased upon frozen storage due to protein denaturation. Results provide important information regarding the opportunity of frozen storage of insect larvae for both research and industrial purposes.